Neuromuscular and metabolic characteristics of elite basketball referees - Bonganha, V.; Cavaglieri, C. R.; Daniel, J. F.; Mercadante, L. A.; Montagner, P. C.; Borin, J. P. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The dynamics of Basketball refereeing has changed and more recently the championships started to use the participation of three referees, but there is still a lack of information about the physical characteristics and performance of the referees. The aim of this study was to characterize the neuromuscular and metabolic performances and body composition of Brazilian elite basketball referees, with a level of national and international refereeing. Methods: Thirty-seven referees participated in the study (international level N=17 and national level N=20). We evaluated anthropometric and body composition variables, among them: height, body mass, body mass index (BMI) and body fat (%); metabolic parameters: lactate at rest and post-exercise; and neuromuscular performance: speed, explosive lower limbs strength, flexibility and aerobic capacity. The main results showed a statistically significant difference in age, in which the international referees were older than the national level (41.94±6.71; 37.30±7.23; P=0.036). Results: There were not significant differences between the levels for neuromuscular and metabolic parameters and body composition. Comparing the results with athletes, the referees showed lower neuromuscular and metabolic parameters and the body composition showed higher body fat than basketball players. Conclusion: These data may represent physiological parameters to be considered in the prescription of physical training during the preparation and competition period.